The pitfalls of in vivo imaging techniques: evidence for cellular damage caused by synchrotron X‐ray computed micro‐tomography. Issue 1 (24th July 2018) - Petruzzellis, Francesco; Pagliarani, Chiara; Savi, Tadeja; Losso, Adriano; Cavalletto, Silvia; Tromba, Giuliana; Dullin, Christian; Bär, Andreas; Ganthaler, Andrea; Miotto, Andrea; Mayr, Stefan; Zwieniecki, Maciej A.; et al.
Summary: Synchrotron X‐ray computed micro‐tomography (microCT) has emerged as a promising noninvasive technique for in vivo monitoring of xylem function, including embolism build‐up under drought and hydraulic recovery following re‐irrigation. Yet, the possible harmful effects of ionizing radiation on plant tissues have never been quantified. We specifically investigated the eventual damage suffered by stem living cells of three different species exposed to repeated microCT scans. Stem samples exposed to one, two or three scans were used to measure cell membrane and RNA integrity, and compared to controls never exposed to X‐rays. Samples exposed to microCT scans suffered serious alterations to cell membranes, as revealed by marked increase in relative electrolyte leakage, and also underwent severe damage to RNA integrity. The negative effects of X‐rays were apparent in all species tested, but the magnitude of damage and the minimum number of scans inducing negative effects were species‐specific. Our data show that multiple microCT scans lead to disruption of fundamental cellular functions and processes. Hence, microCT investigation of phenomena that depend on physiological activity of living cells may produce erroneous results and lead to incorrect conclusions.